Field and glass-house screening of okra (Hibiscus esculentus) genotypes for yield and intercropping - RAJI, J A (The Indian Journal of Agricultural Sciences, 2013)
A field and glass-house experiment was conducted during 1988 and 1989 to study mozphological, physiological and yield attributes of 15 cultivars of okra (Hibiscus esculentus L.) and to identify suitable cultivars for intercropping. Significant differences were recorded for days to flowering, leaf-stalk length, plant height, pod length and diameter and pods/plant among the cultivars. However, they did not show significant differences fornodes/plant and 100-seed weight. The cultivars with late maturity, short internode length, medium to tall height, few (approximately 20) fruiting peduncles/plant, short fruiting-peduncle length (approximately 4 cm), and less than 3.0 cm pod diameter were high yielding. Pod yield had highnegative correlation with days to flowering,leaf nodes/plant, fruiting peduncles/plant and pod length. Only 3 cultivars ('NIIAe 47-4', 'UI92' and 'UI 104') gave higher yields than the other cultivars and were found suitable forintercropping due 10 the possession of medium or short pod length with flabby or weak spines.